«Copiati esattissimamente in misura rigorosa»: note sulle prime incisioni dei dittici eburnei del Tesoro del Duomo di Monza. Anton Francesco Gori, Anton Francesco Frisi e i fratelli Trivulzio nella seconda metà del Settecento (ACME, 2023)
The Treasury of Duomo of Monza preserves three famous ivory diptychs part of liturgical furnishings which belonged to Berengario of Friuli (10th century): diptych of Stilicho and diptych of the Poet and the Muse, both Late Antique, and diptych of King David and St. Gregory, more controversial in dating and interpretation (6th century and Carolingian Age). Anton Francesco Gori is the first editor of the diptychs: he published them into the second volume of Thesaurus veterum diptychorum consularium et ecclesiasticorum (1759), furnishing it with three plates by Andrea Scacciati. Although he never viewed them, the Florentine erudite focuses on a wide critical examination of the artefacts based mainly on the watercolours painted by Girolamo Ferroni, who was hired by the Milanese marquis and precious mediator Alessandro Teodoro Trivulzio. In 1794, the canon Anton Francesco Frisi, who is considered the father of Monza’s historiography, decides to re-edit the diptychs in the third volume’s opening of his Memorie storiche di Monza e sua corte. Advised by don Carlo Trivulzio, erudite and owner of a rich unit of ancient ivories and supported by Giulio Cesare Bianchi’s humble engravings, Frisi offers a reading which clarifies and partially confirms what Gori wrote before, reading that is mildly argumentative about «chi non ha esaminati personalmente i Monumenti, sui quali ragiona». Considering on the background the cultural context of the time and the personalities who got involved, alongside the help of the documents divided by Veneranda Biblioteca Ambrosiana in Milan, Fondazione Trivulzio Archives and Biblioteca Marucelliana in Florence, this paper aims to propose a reconstruction of the events, focusing on the connection between the original version (the diptychs) and the copy (drawings and etchings that followed).